Analisis Penerapan Sosialisasi dan Implementasi Kesehatan dan Keselamatan Kerja serta Pencegahan Kecelakaan Kerja Untuk Keberhasilan Pembangunan Proyek Konstruksi - Ferdiyanto, Anggi; Rochmanto, Decky; Wakit, Ahmat (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2024)
An Occupational Safety and Health (K3) program for workers is very necessary for workers. Especially in the work environment which has a high risk of work accidents and work-related diseases, because work accidents in the construction sector are not only caused by the system that has been implemented by the company but also the awareness of each individual to avoid work accidents. The socialization and implementation of occupational health and safety (K3) as well as work accident prevention programs on the Ash Phond and Aro Wwtp development projects have not yet been implemented optimally, because there are still many workers who are not aware of the importance of the K3 program. The aim of this research is to find out and analyze the implementation of socialization and implementation of K3 and prevention of work accidents for the successful construction of the Ash pond & Aro Wwtp project at the company PT. Murinda Iron Steel (PLTU) Tanjung Jati B Jepara.